1980
DOI: 10.1111/j.1095-8339.1980.tb01985.x
|View full text |Cite
|
Sign up to set email alerts
|

The typification of Erica ciliaris L., of E. tetralix L. and of their hybrid, E. X watsonii Bentham

Abstract: The type specimens of Encn Ci/Zarti, E. tetralix and of E . x watsonu are located. The variant of E. cilzaris without glandular hairs o n its stems and leaves is chosen as the lectotype of the species; the lecrorvpe o1 t;. /r/ralzx ia glandular-haired, as is that ofE. x watsonii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The type is eglandular (McClintock, 1980b), although nearly all the cultivars are glandular. This species has weak stems, but against a spruce tree a plant has reached over 1.8m on Soussons Downs in Devon (where the colony was planted), and have been seen nearly as tall against a pine tree in Spain.…”
Section: E Ciliaris Lmentioning
confidence: 98%
See 2 more Smart Citations
“…The type is eglandular (McClintock, 1980b), although nearly all the cultivars are glandular. This species has weak stems, but against a spruce tree a plant has reached over 1.8m on Soussons Downs in Devon (where the colony was planted), and have been seen nearly as tall against a pine tree in Spain.…”
Section: E Ciliaris Lmentioning
confidence: 98%
“…This is widespread, petering out east in the Eastern Baltic, but does not grow further south than N. Spain. The type is glandular (McClintock, 1980b), but since glandular and eglandular plants grow side by side, both flourishing, one wonders what the value of glands is.…”
Section: E Tetralix Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these spectral fitting methods, many authors have carried out estimations of BH spin (see e.g. Mc-Clintock & Remillard 2006;Middleton et al 2006;Done et al 2007;McClintock et al 2007;Miller 2007;Shafee et al 2008;McClintock et al 2010McClintock et al , 2011McClintock et al , 2014. Abramowicz et al (2004) have suggested that detections of 3:2 QPOs could provide a basis for another method for the determination of masses of BH sources such as the active galactic nuclei and ultraluminuos X-ray sources.…”
Section: Introductionmentioning
confidence: 99%
“…352. 1753. McClintock (1980 provided a discussion of the typification of this name and selected sheet 498.24 LINN as the lectotype.…”
mentioning
confidence: 99%